(untitled) (Confluenţe Bibliologice, 2013)
Metropolitan Efrem Enăchescu was an illustrious personality. He was a Bishop of Bessarabia from 1941-1944. He was born in 1893 in Vîlcea county. He took vows in 1908 and carried on an extensive ecclesiastical activity. He is the author of works: An overview of Christian monarhism (2 volumes), Râmnicu Vâlcea, 1933-1934, 223 + 236 p.; On the relics of the ancestors, Bucharest 1938, 176 p. Efrem Enăchescu died in 1968 at the monastery Cernica. The name of this precursor deserves to be known by all believers in Moldova.